Promotive and Preventive Health Practice and Self-construal - (:unkn) unknown (My University, 2014)
This study investigated the role of established cultural constructs of self-identification in predicting specific motivations for participating in six physical exercise activities. Composite scores were calculated for each participant (n = 223) for each theoretical construct: holism (organic holism, relational holism, and whole-part attention), collective constructionist self-construal (independent vs. interdependent), and regulatory self-focus orientations (promotive vs. preventive). Hierarchical multiple regressions were performed to determine suitability of these constructs in explaining exercise behaviors. Results suggest that the constructs have some influence over individual health choices, but that this influence may be less pronounced than other phenomena in the sample. Other results show significant relationships between the cultural constructs, themselves, confirming previous assumptions regarding the existing theories. Implications for intercultural communication and healthcare are discussed.
Keywords: Cultural Dimensions; Health Communication; Holism; Intercultural Communication; Regulatory Self-focus; Self-construal